The Role of Intellectual Capital in Shaping Innovation in Organizations - Marcin HOFMAN; Jacek WINIARSKI (Communications of International Proceedings, 2022)
The article is theoretical in nature, and its purpose is to present two economic categories: innovation and intellectual capital, and to examine the interdependencies that exist between them. The aim of the paper is to present the role of intellectual capital as the most important concerns of each organization and its role in the shaping innovation in organizations. Based on an analysis of Schumpeter's contribution to economics the concepts of innovation and intellectual capital were analysed in detail, and on this basis the role played by intellectual capital in shaping innovation was analysed. The questions of motives of introducing innovations in enterprises were also touched upon. In this paper the important of innovation and its crucial role in success of organizations is discussed. Authors also emphasize necessity of investment to the human capital as a part of intellectual capital.
Keywords: Innovation; Innovativeness; Intellectual Capital; Competitive Advantage